THE SOCIAL COST OF TRAFFIC CONGESTION AIR POLLUTION (A CASE STUDY ON AHMAD YANI STREET, SURABAYA) - A. Wicaksono (Lowland Technology International, 2009)
At present, Indonesia is facing several problems related with transportation system, especially highway transportation system. The increase of population, followed by the increase of income per capita has caused a significant increase in the growth of motor vehicles in Indonesia, especially that of motorcycles which is very high. Ahmad Yani street is one of Surabaya City’s main entry access roads, of which the traffic burden is the highest. This traffic congestion surely causes high air pollution along the street. Therefore, a study on estimating social cost of air pollution caused by the densely motor vehicle traffic in Ahmad Yani street is considered necessary. The objectives of this study are not only (a) to analyse the peak-hour traffic performance, but also (b) to estimate the cost of air pollution caused by the emmision of motor vehicles in Ahmad Yani street. In this reserach, the methodology of Indonesian Highway Capacity Manual is used to analyse the traffic performance. Due to the inavailabity of Indonesian method, a US method is adopted to estimate the quantity of emission and the cost of air pollution. The cost of air pollution is measured based on the journey length and the average vehicle speed. The result of study shows that traffic congestion is very high in the morning peak hours (07.00-09.00) and is almost evenly happens along the Ahmad Yani street; at some points it even reaches the F level of service. Further result shows that the highest air pollution based on the journey length happens in segment III (GIANT Mall) on Thursday (May, 24th 2007; 07.00-09.00) reaching a cost of Rp. 246,575,690.-. The average vehicle speed is the highest in segment II (DOLOG Office) on Monday (May, 21th 2007; 07.00-09.00) reaching a cost of Rp. 254.431.756,-. In the case of segment II, if it is estimated that the ideal condition is the average speed of 40 kph (max speed allowed inside the city based on traffic law) then the cost of air pollution is Rp. 116.875.678,-, therefore the difference is Rp. 137.556.078,-. This implies that about Rp. 500 billion is needed annually for a one-way traffic. It is recommended that utilizing several measures in traffic management, such as road pricing, traffic divertion and frontage road development is necessary for the reduction of the cost of air pollution.